Depletion and refertilization of the Tethyan oceanic upper mantle as revealed by the early Jurassic Refahiye ophiolite, NE Anatolia-Turkey - Uysal, Ibrahim (2015)
We present new whole-rock major and trace element, Re-Os isotope and mineral chemistry data for the upper mantle peridotites and mafic rocks in the Rehafiye ophiolite in NE Anatolia (Turkey), and discuss their significance for the mantle evolution in Neotethys. The Refahiye peridotites include clinopyroxene (cpx)-rich and cpx-poor harzburgites. Assuming an initial fertile mantle composition, the cpx-rich harzburgites have a limited range of Cr-spl Cr# (33-38), implying 14-18% melt extraction. However, TiO2 contents of the Cr-spl in these rocks are too high (up to 0.24wt.%) to explain their Ti concentrations with a simple melt extraction model in a mid-ocean ridge (MOR) setting, and suggest re-crystallization from an impregnating fertile melt. The interstitial phases of cpx in these samples have high TiO2 (up to 0.40wt.%) and Na2O (up to 0.25wt.%) contents. They also contain interstitial pargasitic amphibole with TiO2 contents varying between 0.69 and 0.88wt.%. These textures and the mineral chemistry data indicate refertilization of the previously depleted, MOR-type peridotites by percolating hydrous melts. The whole-rock REE partial melting modeling is consistent with slightly lower degrees of mantle melting (~12-14%) compared to the melt extraction degrees obtained from the Cr-spl compositions (~15%). Chromian spinel (Cr-spl) phases in the cpx-poor harzburgites show a wider variation of Cr#, ranging between 57 and 75, and reflect 30-40% of partial melting. In contrast, the whole-rock geochemistry of these rocks represents slightly lower degrees of partial melting, varying between 30 and 35%. The enrichment of TiO2 contents of the Cr-spl (up to 0.20wt.%) in some of the cpx-poor harzburgites can be explained by their interaction with Ti-rich hydrous melt formed at supra-subduction (SSZ) tectonic setting. Highly unradiogenic Os isotope composition (0.11956) of a cpx-poor harzburgite sample suggests an ancient melt depletion event experienced by these rocks, whereas its high Re content is a manifestation of subduction enrichment. The mafic units of the Refahiye ophiolite show MORB-like to island arc tholeiite (IAT) geochemical signatures typical of SSZ oceanic crust. A U-Pb zircon age of 183±1Ma obtained from an isotropic gabbro sample suggests that the crystallization of the SSZ-type mafic units in the Refahiye ophiolite is as old as the early Jurassic.